Studi Molecular Docking Senyawa Diterpen Abieten terhadap Enzim Protease Utama (Mpro) Virus Corona - Teruna, Hilwan Yuda; Rullah, Kamal; Khatami, Fajri (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2020)
Coronavirus disease or Covid-19 is a disease caused by a new type of coronavirus, SARS-CoV-2. This disease discovered for the first time in Wuhan, China and has now become a pandemic to the world. This study aims to find compounds that have a potential to inhibit the main protease enzyme (Mpro) of the coronavirus (PDB ID: 6LU7 and 2GTB) through a computational molecular docking modeling approach to abietane diterpenoid derivatives. The molecular docking study was carried out using Autodock4 software and visualized using PyMOL and Discovery Studio. Method validation or redocking showed good accuracy with a root mean square deviation (RMSD) value of 1.85 Å for the 6LU7 enzyme and 1.92 Å for the 2GTB enzyme. The molecular docking study of 3 derivatives of abietane diterpenoid (6-acetyl-7-hydroxyroileanone, 7-hydroxyroileanone and another abieten (CH-6)) showed the binding energy values ​​were -9.07; -8.22 and 7.94 kcal/mol, for enzyme 2GTB showed the binding energy values were -9.54; -9.14; -8.26 kcal/mol. These results indicate the 6-acetyl-7-hydroxyroileanone and 7-hydroxyroileanone compounds have a stronger affinity for the main protease enzyme (Mpro) and the main peptidase enzyme compared to the original ligand which have binding energy of -7.38 and -7.97 kcal/mol. In addition, the type of hydrogen bond in 6-acetyl7-hydroxyroileanone has 6 bonds which are the same as the hydrophilic bond in the native ligand. This research predicted that the 6-acetyl7-hydroxyroileanone compound can be used as an inhibitor of the Covid-19 main protease enzyme (Mpro) and main peptidase enzyme SARS-CoV that has strained previously.